INVESTIGATING STUDENTS’ PERCEPTION OF SPEAKING ACTIVITIES IN THE XI GRADE OF SMA NEGERI 19 MBD - Intopiana, Angelina; Nikijuluw, Renata C. G. V.; Monica, Monica (Koli Journal : English Language Education, 2021)
This study investigated students' perceptions of speaking activities in XI Grade of SMA Negeri 19 Maluku Barat Daya. The data was obtained by a survey conducted from September 23rd to October 25th, 2021. The number of respondents who participated in this study were 33 students who provided information regarding their perception toward English speaking activities they conducted in the classroom. They responded to 15 statements from the questionnaire, which required their perception of speaking activities and types of speaking activities in English class. The study results revealed that the activities carried out in class XI were dominated by group discussions and teacher question and answer (Q &A) sessions. In addition, most respondents consider speaking activity an essential aspect that builds interaction with other people. In general, the respondents asserted that talking in English is fun. From the result of the current study, it is also suggested that there are many aspects that must be taught to students to master speaking skills.